Entering the UN maze - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Even in these inclusive days of consultation with civil society and concertation between public and independent sectors, it is not always easy for a non-official organisation to find its way into the official circuits. First it has to get noticed, or iden